Reunion des partenaires sur l'initiative regionale pour la promotion des aliments locaux des filieres alimentaires traditionnelles Ouest Africaines, Abuja Nigeria, du 18-20 Mai 2010 - Organisation Ouest Africaine de la Santé; Réseau des Organisations Paysannes et des Producteurs Agricole de l'Afrique de l'Ouest; Bioversity International; Food and Agriculture Organization of the United Nations (2010)
Adequate nutrition for the West African population can rightly be perceived as a product of interventions requiring several essential inputs for its development and execution. Vital inputs from several sectors, public and private institutions are required in order to ensure the desired goals of adequate food security, nutrition and health of a population. The need for collaborative partnership is increasingly being recognized in West Africa where during the past four years, a strong regional collaborative, multi-disciplinary and cross-sectoral partnership has developed involving the West African Health Organization (WAHO), the ECOWAS Commission on Agriculture, the regional network of small-scale food producers (Reseau des Organisations Paysannes et des Producteurs Agricole de l’Afrique de l’Ouest – ROPPA), in collaboration with Bioversity International and the United Nations Food and Agriculture Organization (FAO). The overarching objective of this initiative is to ensure, through its activities, the effective promotion of use of local food resources from West Africa’s traditional food systems in households, and in strategies and interventions against food insecurity, micronutrient deficiencies and diet related chronic diseases.